Putting the “Biology” Back into “Neurobiology”: The Strength of Diversity in Animal Model Systems for Neuroscience Research - Keifer, Joyce; Summers, Cliff H. (Frontiers in Systems Neuroscience, 2016)
Current trends in neuroscience research have moved toward a reliance on rodent animal models to study most aspects of brain function. Such laboratory-reared animals are highly inbred, have been disengaged from their natural environments for generations, and appear to be of limited predictive value for successful clinical outcomes. In this Perspective, we argue that research on a rich diversity of animal model systems is fundamental to new discoveries in evolutionarily conserved core physiological and molecular mechanisms that are the foundation of human brain function. Analysis of neural circuits across phyla will reveal general computational solutions that form the basis for adaptive behavioral responses. Further, we stress that development of ethoexperimental approaches to improve our understanding of behavioral nuance will help to realign our research strategies with therapeutic goals and improve the translational validity of specific animal models. Finally, we suggest that neuroscience has a role in environmental conservation of habitat and fauna that will preserve and protect the ecological settings that drive species-specific behavioral adaptations. A rich biodiversity will enhance our understanding of human brain function and lead in unpredicted directions for development of therapeutic treatments for neurological disorders.